2020
DOI: 10.1038/s41598-020-77723-6
|View full text |Cite
|
Sign up to set email alerts
|

Pan-genome analysis and ancestral state reconstruction of class halobacteria: probability of a new super-order

Abstract: Halobacteria, a class of Euryarchaeota are extremely halophilic archaea that can adapt to a wide range of salt concentration generally from 10% NaCl to saturated salt concentration of 32% NaCl. It consists of the orders: Halobacteriales, Haloferaciales and Natriabales. Pan-genome analysis of class Halobacteria was done to explore the core (300) and variable components (Softcore: 998, Cloud:36531, Shell:11784). The core component revealed genes of replication, transcription, translation and repair, whereas the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 76 publications
4
15
0
Order By: Relevance
“…Phylogenomic trees inferred from the concatenation of the 525 amino acid sequences of the orthologous single-copy genes present in the type strain genomes (Figure 2) and in all the genomes under study (Supplementary Figure 1) were obtained. A previous study focused on the evolution of the class Halobacteria has also reported phylogenomic core trees that concurs with our results, although those phylogenetic reconstructions were based on only 45 orthologous core genes and did not include all the representative genomes within the Natrialbales (Gaba et al, 2020). As might be expected, the topology of our phylogenomic tree was not totally in agreement to the 16S rRNA gene phylogeny, but the clusters obtained were better supported in the phylogenomic tree, with 100% bootstrap in almost all bifurcations.…”
Section: Taxophylogenomics and Overall Genome Related Indexes Values Prove The Proposal To Keep The Genera Natrinema And Haloterrigena Assupporting
confidence: 91%
See 1 more Smart Citation
“…Phylogenomic trees inferred from the concatenation of the 525 amino acid sequences of the orthologous single-copy genes present in the type strain genomes (Figure 2) and in all the genomes under study (Supplementary Figure 1) were obtained. A previous study focused on the evolution of the class Halobacteria has also reported phylogenomic core trees that concurs with our results, although those phylogenetic reconstructions were based on only 45 orthologous core genes and did not include all the representative genomes within the Natrialbales (Gaba et al, 2020). As might be expected, the topology of our phylogenomic tree was not totally in agreement to the 16S rRNA gene phylogeny, but the clusters obtained were better supported in the phylogenomic tree, with 100% bootstrap in almost all bifurcations.…”
Section: Taxophylogenomics and Overall Genome Related Indexes Values Prove The Proposal To Keep The Genera Natrinema And Haloterrigena Assupporting
confidence: 91%
“…Currently, the class Halobacteria comprises three orders (i.e., Halobacteriales, Haloferacales, and Natrialbales), six families (i.e., Halobacteriaceae, Haloarculaceae, Halococcaceae, Haloferacaceae, Halorubraceae, and Natrialbaceae), 72 genera and 289 species whose names have been validly published (Parte et al, 2020), reflecting the high diversity and complex phylogenetic relationships within the haloarchaea. In fact, recent pan-genome analysis and ancestral state reconstruction has brought to light the heterogeneity of this class, which possesses an open pan-genome, and the occurrence of genome expansion and horizontal gene transfer during the evolution of Halobacteria (Gaba et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The second most abundant category of genes in the pan-genome was general function predicted only including 989 genes and then by genes related to transcription (K) including 803 genes. The over representation of "poorly characterized genes" and "general function predicted only" in the COG categories is similar to what has been observed in other pan-genome studies (Sood et al, 2019;Gaba et al, 2020;Motyka-Pomagruk et al, 2020). Regulation at the transcriptional initiation level is probably the most common scenario for metabolic adaptation in bacteria (Leyn et al, 2013;Arrieta-Ortiz et al, 2015).…”
Section: The Pan-genome Of the Bp Bacteriasupporting
confidence: 83%
“…It consists of three orders: Halobacteriales , Haloferacales , and Natrialbales , which include six families and more than 50 genera [ 5 , 70 ]. A recent pan-genome analysis and ancestral state reconstruction of the class Halobacteria suggest a new super-order comprising of Natrialbales and Halobacteriales [ 71 ]. Our study in Tuz Lake has shown that eleven haloarchaeal genera are part of the microbiota of this environment ( Table 2 and Figure 3 ), and that they are very diverse with respect to their taxonomic affiliations.…”
Section: Discussionmentioning
confidence: 99%